2006
DOI: 10.1590/s1413-86702006000600008
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of Brazilian Amazon plant extracts

Abstract: Infections caused by multiresistant bacteria are a widespread problem, especially in intensive care units. New antibiotics are necessary, and we need to search for alternatives, including natural products. Brazil is one of the hottest spots in the world in terms of biodiversity, but little is known about the chemical and pharmacological properties of most of the plants found in the Amazon rain forest and the Atlantic Forest. We screened 1,220 organic and aqueous extracts, obtained from Amazon and Atlantic rain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 7 publications
4
18
0
2
Order By: Relevance
“…73 (1) , but when the natural product was associated with the aminoglycosides, a synergistic or antagonistic antibiotic activity was detected against both bacterial strains assayed. When compared with the results of SUFFREDINI et al (2006), the results observed on this work indicate a better antibacterial activity.…”
Section: Resultssupporting
confidence: 57%
“…73 (1) , but when the natural product was associated with the aminoglycosides, a synergistic or antagonistic antibiotic activity was detected against both bacterial strains assayed. When compared with the results of SUFFREDINI et al (2006), the results observed on this work indicate a better antibacterial activity.…”
Section: Resultssupporting
confidence: 57%
“…Although it is not recommended to compare the biological activity of standard drugs such as fluconazole with the activity of a complex mixture of substances (Suffredini et al, 2006), the zones of inhibition of crude extracts for C. erythrocarpos and S. ellipticum and fractions DS 3 and DS 5 against A. niger were relatively comparable to that of fluconazole. The MIC and MFC values for these extracts were, however, not comparable to the standard except for fraction DS 3, which was relatively comparable against C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the antibacterial activities from other plant extracts, several C. bernieri extracts were more efficient than methanolic aerial part extracts of Inula viscosa against B. subtilis (MIC=25 mg/ml, MBC=50 mg/ml) and S. aureus (MIC=12.5 mg/ml, MBC=50 mg/ml) (Larbi et al, 2016). By contrast, tuber ethyl acetate extract of Tropaeolum pentaphyllum against E. coli (MIC=0.02 mg/ml, MBC=0.64 mg/ml), P. aeruginosa (MIC=0.04 mg/ml, MBC=0.64 mg/ml) (da Cruz et al, 2016) and organic extract (aerial parts) of Rapanea parvifolia against E. faecalis (MIC=0.03 mg/ml, MBC=0.06 mg/ml) (Suffredini et al, 2006) were more efficient. On fungi, LME (MIC=0.097 mg/ml, MFC=0.195 mg/ml) was more efficient than leaf methanolic extract of Myrtus nivellei against C. albicans (MIC=4.5 mg/ml) (Touaibia and Chaouch, 2015) whereas LME, SEA and SME against C. guilliermondii (MIC=0.08 mg/ml, MFC=0.32 mg/ml) were less efficient than ethyl acetate extract of T.…”
Section: Discussionmentioning
confidence: 89%